Nekrolog over Gustav Albeck - Michelsen, William (Grundtvig-studier, 1995)
Gustav Albeck 1906 - 1995 By William Michelsen William Michelsen writes an obituary of Gustav Albeck, Professor of Nordic Literature. In his commemorative words, William Michelsen quotes at some length from the commemorative speech, made by Bishop Henning Høirup, Doctor of Divinity, on the occasion of Gustav Albeck’s funeral in the Cathedral of Aarhus.In his commemorative speech Bishop Høirup describes Gustav Albeck’s close ties to Aarhus, where his father, Chief Consultant Viggo Albeck, was the prime mover behind the foundation of the University of Aarhus. Thus, Gustav Albeck’s first publication after his university graduation in 1932 was a pamphlet about the history of the establishment of the Jutland university. The paper is evidence of a fundamental feature of Gustav Albeck’s personality: his loyalty to the family, and to the heritage from previous generations. It is emphasized by Henning Høirup that Gustav Albeck’s research work covered a wide field from runic inscriptions to modem Danish 20th century literature, and that his personal commitment and sympathetic insight combined seriousness with humour, most often inextricably linked together. As an expert on Danish Golden Age literature Albeck was superb. Høirup describes Gustav Albeck’s inspiring work in the Grundtvig Society from its foundation, and his 43 years as editor of Grundtvig Studier, the high scholarly standards of which were of paramount importance for him. Finally Bishop Høirup tells about Gustav Albeck’s invaluable work to promote classical music in Aarhus, and he concludes his speech by remarking on the joy felt by Albeck over the gift to man received in baptism, and his love of Danish poetry.Subsequently William Michelsen draws an equally personal portrait of Gustav Albeck and his work in literary history, in Grundtvig scholarship and popular enlightenment. Gustav Albeck took his M.A. degree in Nordic philology in 1932, and became a Doctor of Philosophy with his thesis on the Nordic Kings’ sagas in 1946, and in 1959 he was appointed Professor at the University of Aarhus, after having been on the teaching staff for a number of years. As early as 1934 Grundtvig wrote his first study of Grundtvig’s early poetry, and through the 1940s he published a number of shorter books on Grundtvig’s writings. In 1948 he contributed to the first annual volume of Grundtvig Studier, and in 1951 he became the editor of the yearbook, a post he held until his death.William Michelsen suggests that Gustav Albeck’s Grundtvig research should be seen on the background of Grundtvig’s visions of a new Danish university, unhampered by rigid academic traditions - visions that found expression in Grundtvig’s folk high school thoughts and his ideas of a Scandinavian university in Gothenburg. Gustav Albeck regarded the University of Aarhus and the University Extension Institution as realizations of these ideas. He agreed with Grundtvig about the crucial importance of popular enlightenment, but always preserved an objective and matter-of-fact distance to the ideas in Grundtvig’s writings. What was important to Gustav Albeck in literary studies was to state what literature says, not to evaluate it or relate oneself personally to it. Thus, to him it was essential to emphasize that Grundtvig was a poet and a great poet - a visionary poet who remained critical towards his own time. Albeck’s philological approach to literary scholarship finds expression in his work on Grundtvig manuscripts, such as the publication of .Grundtvig’s diaries and extract collections. in 1979. Albeck’s most significant book as a Grundtvig scholar was published in 1955 in the series Acta Jutlandica, entitled .Around Grundtvig’s Poetry Collections.. This book deals with Grundtvig’s poetical works in the years 1808-1816, but also contains a large amount of material that throws light on Grundtvig’s development over these years.Fundamentally important to Grundtvig research is Gustav Albeck’s preparation of a model for the registration of Grundtvig’s posthumous works, used by the group of scholars who worked out the 30-volume register. Gustav Albeck’s greatest book is his last publication, .University and People., from 1984, with the modest subtitle .Contributions to the History of the University Extension Institution.. The book contains a wealth of information about how Grundtvig’s vision of a people’s university became a reality around the turn of the century. For 30 years Gustav Albeck was the president of the University Extension Institution in Aarhus.William Michelsen concludes his obituary of Gustav Albeck by pointing out that as Albeck saw him, Grundtvig was not so different from his own time as we tend to see him today. And Gustav Albeck could finish his chapter on Grundtvig in the Politiken Literary History by quoting Jørgen Elbek saying that Grundtvig, with his unshakable faith in the word, was a poet in a far more exclusive sense than any of his contemporaries.